2006
DOI: 10.1080/10903120600726007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Infant-Safe Homes in a Community Injury Prevention Program

Abstract: An alarmingly low number of homes were infant safe (n = 24) and the number of children in the home did not seem to affect home safety. Further research is needed to determine the efficacy of the "Welcome to the World" program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous studies on the home environment found serious deficiencies in the presence and use of home safety devices. 34,35 Although creating a safe environment is important (eg, properly installing stair gates), this alone is not sufficient. Parental knowledge of developmental motor milestones is often lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the home environment found serious deficiencies in the presence and use of home safety devices. 34,35 Although creating a safe environment is important (eg, properly installing stair gates), this alone is not sufficient. Parental knowledge of developmental motor milestones is often lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The search identified 3,004 articles, and, after screening and searching bibliographies of included articles, a total of 64 studies representing 58 unique community paramedicine programs were included (Figure 1). 1,2,3,6,7, There were 15 (23.4%) of the 64 studies identified by hand-searching the bibliographies of included studies and by follow-up grey literature searching, and 14 (24.1%) of 58 community paramedicine programs captured were identified through the grey literature (see online Appendix for the table of included studies and grey literature sources).…”
Section: Part I Search Yieldmentioning
confidence: 99%
“…5 Programs can be tailored to community needs by providing a range of services, including disease management, home assessments, and referral to community services. 6,7 Community paramedicine programs may lead to more effective use of paramedic resources. In some programs, paramedics on accommodated duty have adopted the community paramedic role while awaiting return to regular duties.…”
Section: Introductionmentioning
confidence: 99%
“…Two US articles described an intervention where paramedics provided education to new and expectant parents on childhood injury prevention [ 30 , 31 ]. However, no information was provided about whether the intervention changed behaviour in the long-term or had any impact on subsequent injuries sustained in the home.…”
Section: Resultsmentioning
confidence: 99%